Effects of kognitive and physical exercise on soccer penalty kicking. An exploratory study - Weigelt, M.; Machlitt, D.; van der Kamp, J.; Noel, B.; Memmert, D. (Journal of Applied Sport and Exercise Psychology, 2024)
Abstract: This exploratory study examined the effects of previous exercise on goal-side selection in soccer penalty kicking. Two types of 30-min exercise were tested and compared with a control group in an off-center paradigm. The cognitive-exercise group performed the d2 test of attention and the physical-exercise group rode on a fitness bicycle. In the off-center paradigm, participants viewed images of a goalkeeper in a soccer goal, who stood either in the middle of the goal or slightly displaced to the left or right. During the experiment, all participants selected the greater goal side for kicking when they perceived the goalkeeper`s position in the middle of the goal (i. e., off-center effect). However, only participants of the cognitive-exercise group demonstrated a strong bias for the right goal side, indicating visual-spatial pseudoneglect for the goalkeeper position. Therefore, only previous cognitive and not physical exercise appears to affect perception and decision-making in soccer penalty kicking.